Search interfaces for biomedical searching: How do gaze, user perception, search behaviour and search performance relate? - Liu, Ying-Hsang; Thomas, Paul; Gedeon, Tom; Rusnachenko, Nicolay (ACM SIGIR Conference on Human Information Interaction and Retrieval, 2022)
The objective of this controlled information retrieval (IR) user experiment is to gain an understanding of domain experts' interactions with novel search interfaces within the context of biomedical information search, with a goal of better search interface design. In this paper, we examine the relationships among user perception, gaze and search behaviour and user search performance. An eye-tracking study of biomedical domain experts' interactions with novel search interfaces was conducted. A total of thirty-two users participated and searched for documents answering eight complex exploratory search tasks, using four different search interfaces. The findings suggest that gaze behaviour in terms of fixation durations based measures of areas of interest (AOI), i.e., visual attention to the elements of title, author, abstract and MeSH (Medical Subject Headings) terms in document surrogates is correlated with search performance. Users are more likely to achieve better search performance by precision-based measures when 1) search tasks are perceived as difficult; 2) users attend to the element of abstract; and 3) users can recall using the per-query suggestions during the search processes. More importantly, our findings suggest that a user search interface design that displays contextual information between the suggested keywords and the document may better support users reformulating their queries for complex search tasks in the biomedical domain. We discuss implications for the design of search user interfaces for biomedical searching.